Inequalities for L_p Quasi Norm with Application in Number Theory - et. al., Sahab Mohsen Aboud, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Some author used the number theory in functional analysis and estimated some upper bounds for functions in and spaces. Here we denoted our work to prove some multiplicative inequalities for functions in quasi normed spaces, that we can considered that the and as special cases of our case. These inequalities in analysis and number theory.